Determination of Factors Affecting Shipping Safety Performance: Study Literature Review - Chandra Mardhika Saputra; Abdullah Ade Suryobuwono; Primadi Candra Susanto (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The purpose of this study is to develop hypotheses related to factors that influence shipping safety performance, especially in the maritime transportation sector in Indonesia. The approach used in this literature review is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The technique used in this literature review is comparative analysis. The data used in this descriptive qualitative approach were obtained from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Web of Science, Sinta 2-5 Journal, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books. The results of this literature review are: 1) Bridge resource management influences maritime safety performance; 2) Facilities and infrastructure influence maritime safety performance; 3) Crewing competence influences maritime safety performance; and 4) Fleet seaworthiness influences maritime safety performance.